2001
DOI: 10.1099/0022-1317-82-2-367
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination of chronic hepatitis B virus carriers with preS2/S envelope protein is not associated with the emergence of envelope escape mutants

Abstract: PreS2/S vaccination of chronic hepatitis B virus (HBV) carriers led to a reduction in HBV replication or clearance of virus in 30 % of treated patients. This study assessed whether vaccinotherapy of chronic HBV carriers induced the selection of escape mutants in the envelope ' a ' determinant and whether envelope genetic variability might affect the response to vaccination. No amino acid differences were observed in the ' a ' determinant between sequences obtained before and after treatment (five responders an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 28 publications
2
3
0
Order By: Relevance
“…The presence of T118V and A128V were found significantly in HBV/D2, which concurs with our previous study [51] and hence are considered as signature residues of this subgenotype. Additional mutation outside the MHL region was also observed including the E164G mutation, which was earlier reported by another study on chronic HBV carriers [52] . However, its implication as a vaccine escape mutant is still unclear.…”
Section: Discussionsupporting
confidence: 76%
“…The presence of T118V and A128V were found significantly in HBV/D2, which concurs with our previous study [51] and hence are considered as signature residues of this subgenotype. Additional mutation outside the MHL region was also observed including the E164G mutation, which was earlier reported by another study on chronic HBV carriers [52] . However, its implication as a vaccine escape mutant is still unclear.…”
Section: Discussionsupporting
confidence: 76%
“…These include mutation V184A, previously detected in children vaccinated against HBV [Chong‐Jin et al, ] and in chronic HBV inactive carriers [Norouzi et al, ]. And also mutation E164G, previously identified in interferon responders, interferon treatment reverters [Gous et al, ], and in a vaccine non‐responder patients [Soussan et al, ]. In the pre‐S1 region, mutation F25L, which has been previously associated with HBsAg negativity in South African patients [Makondo et al, ], was identified in one HBsAg‐negative patient in this study.…”
Section: Discussionsupporting
confidence: 74%
“…For example, the preS-containing Hepacare vaccine was shown to stimulate stronger and more rapid cellular and humoral immune responses and to overcome anti-HBs non-responsiveness [153,154]. Other preS-containing HBs vaccine candidates demonstrated rapid seroprotection [155] and apparently prevented selection of the determinant a escape mutants [156].…”
Section: Prevention and Therapy Of Hepatitis B: A Potential Role For mentioning
confidence: 99%